Problem solving strategies of partitive and measurement division used by students of Primary Education (Edma 0-6: Educación Matemática en la Infancia, 2021)
The main objective of this study is to examine the strategies employed by primary school students when solving problems of measurement division and partitive division with fractions. The participants were 149 students from 1st to 6th grade of Primary Education. The data collection instrument was a questionnaire with four problems: two of measurement division and two of partitive division, which were adapted for each of the educational levels. The results show that students in the first cycle are more successful in the problems of measurement division; in the second cycle, the same success is obtained in both types of problems; and, in the third cycle, students achieve more success in the partitive division. In the same way, the most used strategies in the measurement division problems were the multiplicative ones and direct modeling; while in the partitive division the most used strategies were the additive and multiplicative coordination. In addition, students from the first levels have more variety of strategies than those of the higher levels.
Keywords: Fractions; Levels of success; Measurement division; Partitive division; Primary education; Problems of multiple groups; Strategies